KEPASTIAN HUKUM TERHADAP PENCABUTAN HAK ATAS KEPEMILIKAN TANAH TERLANTAR BERDASARKAN UNDANG - UNDANG POKOK AGRARIA - Perkasa, Prisma Bella Bangkit; Furcony Putri Syakura,; Yudha Cahya Kumala, (Journal of Innovation Research and Knowledge, 2025)
Land has a very strategic function, both as a natural resource and as a space for development, the state has also given land rights or Management Rights to Right Holders to be cultivated, used, and utilized and maintained properly, but in this vast country of Indonesia, there are still a lot of abandoned land and unclear utilization. These abandoned lands tend to be used only as objects of speculation. Jan Michle Otto's Legal Certainty Theory and Boedi Harsono's Abandoned Land are the theoretical frameworks used in this research. This research uses normative juridical research methodology, which is a secondary data search from legal literature collected from primary, secondary, and tertiary sources. The research methods used are statutory, case, analytical, and conceptual research methods. The procedure for collecting legal sources includes cataloging and naming positive legal regulations, books, journals, and other sources of legal information. The construction of analogies, legal refinement, and systematic and grammatical legal interpretation are tools used in the process of analyzing legal materials. The result of the research is that the legal effect of land designated as abandoned land is that its ownership will be erased, but if the decision is considered detrimental to one of the parties, then the legal remedy that can be taken is to file a lawsuit at the State Administrative Court. Legal certainty over abandoned land has been regulated in Law Number 5 of 1960 concerning Basic Agrarian Regulations, strengthened by Government Regulation of the Republic of Indonesia Number 20 of 2021 concerning the Control of Abandoned Areas and Land. The written rules for legal certainty on abandoned land have been clearly detailed in various applicable regulations, but in carrying out the contents of these rules the National Land Agency is considered not optimal in making decisions, considering that there are still many errors in inventorying, identification and there are even mistakes in determining an abandoned land.